2010
DOI: 10.1063/1.3289719
|View full text |Cite
|
Sign up to set email alerts
|

White-emitting oxidized silicon nanocrystals: Discontinuity in spectral development with reducing size

Abstract: Small oxidized silicon nanocrystals of average sizes below 3.5 nm are prepared using modified electrochemical etching of a silicon wafer. Modifications introduced in the etching procedure together with postetching treatment in H2O2 lead to a decrease in the nanocrystalline core size and also, to some extent, to changes in the surface oxide. The interplay between these two factors allows us to blueshift the photoluminescence (PL) spectrum from 680 down to 590 nm, which is accompanied by changes in PL dynamics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 32 publications
3
70
1
Order By: Relevance
“…The common bottom-up approaches are driven by chemical reactions developed from precursors with final reduction treatments [20,21], decompositions based in laser induced pyrolysis [22] or plasma induced thermolysis [23,24]. The usual top-down approaches may include physical methods, as the laser ablation [25,26], ballmilling [27,28] and chemical catalyzed etching [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The common bottom-up approaches are driven by chemical reactions developed from precursors with final reduction treatments [20,21], decompositions based in laser induced pyrolysis [22] or plasma induced thermolysis [23,24]. The usual top-down approaches may include physical methods, as the laser ablation [25,26], ballmilling [27,28] and chemical catalyzed etching [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that a largely disordered system is expected when the size of Si-nps is between 1 and 2 nm. Thus, the small Si-nps are no longer crystalline but amorphous like, as also indicated by theoretical calculations [49,50]. Then, the dispersed Si atoms in the M30 ilms are preferentially arranged as very small Si-nps (E' δ ) and some defects like oxygen-deiciency center (ODC) and NBOHC as reported for thin SiOx ilms (<100 nm) [51].…”
Section: Luminescence -An Outlook On the Phenomena And Their Applicatmentioning
confidence: 78%
“…The prepared silicon nanocrystals with oxidized surface (SiNc:O) have the size of the crystalline core of about 2.5-3 nm [20]. Their photoluminescence (PL) is quite typical for SiNcs as shown in Fig.…”
Section: Silicon Nanocrystals With Oxidized Surfacementioning
confidence: 97%